Betapa Indahnya Kedatangan Mereka Yang Membawa Berita Damai (Yesaya 52:1-12) - Dyulius Thomas Bilo (JURNAL LUXNOS, 2018)
Abstract: It is interesting to study the phrase “how beautiful it is to come with them who bring messages of peace” in the context of the book of Isaiah. This sentence is appropriate to state how God is the savior and liberator for the Israelites who have been punished through exile and slavery to other nations. But in reality not everyone is able to understand the meaning of this expression. In its exploration, this paper aims to explain how the news of Israel's liberation from exile and slavery, how the state of the Israelites in exile and slavery, how God freed them, how beautiful the deliverance or salvation that God did for the Israelites, and how the correlation of Isaiah's message with Micah's message , Nahum, and the Apostle Paul, and how to interpret the expression "how beautiful the arrival of those who bring messages of peace" in the world of Christian education. It was preceded by an introduction covering the division of Isaiah, the meaning of Isaiah's name, and the ministry of the prophet Isaiah. Abstrak: Sangat menarik untuk mengkaji ungkapan “betapa indahnya kedatangan mereka yang membawa berita damai” dalam konteks kitab Yesaya. Kalimat ini tepat untuk menyatakan bagaimana Allah sebagai penyelamat dan pembebas bagi bangsa Israel yang telah dihukum melalui pembuangan dan perbudakan bangsa lain. Namun kenyataannya belum semua orang mampu memahami maksud dari ungkapan tersebut. Dalam eksplorasinya tulisan ini bertujuan menjelaskan bagaimana berita pembebasan Bangsa Israel dari pembuangan dan perbudakan, bagaimana keadaan Bangsa Israel di tempat pembuangan dan perbudakan, bagaimana Allah membebaskannya, bagaimana keindahan pembebasan atau penyelamatan yang Allah kerjakan bagi Bangsa Israel, dan bagaimana korelasi berita Yesaya dengan berita Mikha, Nahum, dan Rasul Paulus, dan bagaimana memaknai ungkapan “betapa indahnya kedatangan mereka yang membawa berita damai” dalam dunia pendidikan Kristen. Sebelumnya didahului pengantar yang mencakup pembagian kitab Yesaya, arti nama Yesaya, dan pelayanan Nabi Yesaya.